2015
DOI: 10.1103/physrevb.91.075307
|View full text |Cite
|
Sign up to set email alerts
|

Band bending driven evolution of the bound electron states at the interface between a three-dimensional topological insulator and a three-dimensional normal insulator

Abstract: In the frame of k · p method and variational approach for the effective energy functional of a contact between a three-dimensional topological insulator (TI) and normal insulator (NI), we analytically describe the formation of interfacial bound electron states of two types (ordinary and topological) having different spatial distributions and energy spectra. We show that these states appear as a result of the interplay of two factors: hybridization and band bending of the TI and NI electron states near the TI/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…In addition, Galanakis et al [27] also suggested that the BB profile and the energy of the Dirac point can be controlled by electrostatic effects. The importance of the BB has been demonstrated in other 2GTI based nanostructures as well, including topological/normal insulator interfaces [29][30][31][32].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, Galanakis et al [27] also suggested that the BB profile and the energy of the Dirac point can be controlled by electrostatic effects. The importance of the BB has been demonstrated in other 2GTI based nanostructures as well, including topological/normal insulator interfaces [29][30][31][32].…”
Section: Introductionmentioning
confidence: 98%
“…The effect of heterostructure formation on the primitive Dirac surface state localized at the interface (henceforth referred to as the 'Dirac interface state') has been investigated for various materials. In the cases of TIinsulator bilayers, first-principles studies have found that interface states localized a bit deeper into the interface appear near the Fermi level E F with Dirac-like dispersion, while the original Dirac surface states are shifted way below E F due to band-bending potentials, which are induced by the mismatch between chemical potentials [8][9][10][11] . As for TI-metal heterostructures, effective model studies have found Dirac interface states becoming diffusive under weak TI-metal coupling 12 while first-principles studies have reported no spin-momentumlocked interface states for various metals 7,13 .…”
Section: Introductionmentioning
confidence: 99%
“…The transitions between the QSHE insulator and trivial band insulator phases have been explored as being driven by alternation of the hybridization gap caused by the 3D TI film thickness [14,[30][31][32][33][34]. At the same time, a proper description of the boundary effects in the TI/NI heterostructures is almost absent, with few exceptions [35][36][37][38][39][40]. The development of the quantum transport theory in these systems requires to answer some principal questions.…”
Section: Introductionmentioning
confidence: 99%
“…Within the framework of continual approach, the influence of the NI slabs on electron states in the sandwiched 3D TI spacer film is taken into consideration through the boundary conditions specified by the effective interface potential (IP), which respects time-reversal symmetry. Such analytic scheme has been developed and successfully used in the previous investigations [37][38][39][40] to show how the changes in the IP could modify the in-gap bound states at the TI/NI interface. In the present theoretical work, we unveil that there are two distinct microscopic mechanisms to drive the transition between the trivial insulator phase and the Hall insulator phase in the NI/TI/NI trilayer.…”
Section: Introductionmentioning
confidence: 99%